Penerapan Rute Distribusi Barang Menggunakan Metode Saving Matrix dan Nearest Neighbor (Study Kasus: AMDK K3PG Gresik ) - Reza Dimas Avianto; Jaka Purnama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Goods distribution is an important activity in company operations, particularly in the bottled drinking water (AMDK) industry, as it affects delivery performance, operational costs, and customer service levels. This study aims to design and analyze distribution route optimization using the Saving Matrix method and the Nearest Neighbor algorithm to improve the efficiency of the company's distribution system. The results show that the implementation of the Saving Matrix method and Nearest Neighbor algorithm successfully improved distribution efficiency at AMDK K3PG Gresik. The total distribution distance was reduced from 296 km to 263 km, resulting in a distance saving of 33 km (11%). In addition, the total distribution operating cost decreased from IDR 1,535,300 to IDR 1,347,300 per day, achieving a cost saving of IDR 188,000 per day (12.2%). Therefore, the combination of the Saving Matrix method and the Nearest Neighbor algorithm proved effective in optimizing the distribution system, reducing operational costs, and improving delivery route efficiency.